2014
DOI: 10.1038/ncomms6339
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-14 and kinesin-5 antagonistically regulate microtubule nucleation by γ-TuRC in yeast and human cells

Abstract: Bipolar spindle assembly is a critical control point for initiation of mitosis through nucleation and organization of spindle microtubules and is regulated by kinesin-like proteins. In fission yeast, the kinesin-14 Pkl1 binds the γ-tubulin ring complex (γ-TuRC) microtubule-organizing centre at spindle poles and can alter its structure and function. Here we show that kinesin-14 blocks microtubule nucleation in yeast and reveal that this inhibition is countered by the kinesin-5 protein, Cut7. Furthermore, we dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
83
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(94 citation statements)
references
References 69 publications
7
83
3
Order By: Relevance
“…A recent report revealed that Cut7 regulates microtubule nucleation at spindle poles, and that its head and tail bind to the g-TuRC (Olmsted et al, 2014). Considering the localization of Cut7-DN2, the N-terminal extension is unlikely to be involved in such g-TuRC binding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent report revealed that Cut7 regulates microtubule nucleation at spindle poles, and that its head and tail bind to the g-TuRC (Olmsted et al, 2014). Considering the localization of Cut7-DN2, the N-terminal extension is unlikely to be involved in such g-TuRC binding.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the localization of Cut7-DN2, the N-terminal extension is unlikely to be involved in such g-TuRC binding. The mechanism by which microtubule nucleation at spindle poles is regulated is thought to be conserved in human cells (Olmsted et al, 2014), and thus Eg5 (human kinesin-5) might associate with the g-TuRC in a similar manner to Cut7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KIFC5A has an additional ATP-independent microtubule-binding domain (Zhang and Sperry, 2004) and Ncd has a positively charged sequence in its tail domain that tethers it to the C-terminal E-hook of tubulin . Mouse KIFC1 has tail domain sequences that target it to membrane-bound organelles (Zhang and Sperry, 2004); the tail domain of Pkl1 direct it to γ-tubulin (Olmsted et al, 2013(Olmsted et al, , 2014. Additional studies in which chimeric kinesin-14 proteins of human HSET, Drosophila Ncd and fission yeast Pkl1 were generated also support this paradigm and confirm that tail domain sequences orchestrate function (Simeonov et al, 2009).…”
Section: Introductionmentioning
confidence: 58%
“…An exception to this is Pkl1, for which the tail domain was shown to be able to regulate nucleation without the motor domain in vitro and in vivo (Fig. 1B), and to do so in yeast and human cells (Olmsted et al, 2013(Olmsted et al, , 2014. Microtubule-dependent D. melanogaster Ncd motors have been shown to localize to parallel microtubules where they exert their movement into the opposite direction, thus creating a 'tug-of-war' effect.…”
Section: Introductionmentioning
confidence: 99%